A pilot clinical trial of adapted tango to improve negative health impacts in middle aged African‐American women caregivers of persons with Alzheimer's disease: Biomarkers (non‐neuroimaging)/Use in clinical trial design and evaluation. (7th December 2020) - Wharton, Whitney; Shin, Ryan; Hu, William T.; Jeong, Leanne; Bay, Allison A.; Hart, Ariel R.; Ni, Liang; Hackney, Madeleine E
Abstract: Background: Dementia caregivers have increased risk for psychological and physiological illness including depression, stress, hypertension, diabetes, diminished QOL, low‐grade inflammation and increased mortality. Dementia risk factors include gender, race and family history. Method: This phase I pilot study evaluated the potential physiological, cognitive, motor, and psychosocial benefits of a 12 week, 20‐lesson adapted Argentine Tango intervention (N=30) to a no‐contact control group (N=10) in middle‐aged (45‐65 years) African American women caregivers of their parent with AD. Blood draw for inflammatory markers was done pre/post intervention/control. Result: Women were middle age (60.0 yrs), slightly overweight (BMI 30.7) and highly educated (16.3 yrs of education). Significant reductions were noted in pre/post visit change for the Tango group in inflammatory markers including TNFα, interleukin‐7 and interferon‐gamma; maintenance of 30s chair stand performance, balance, and performance on the Tower of London and Stroop interference tests. Other non‐significant trends were noted in caregiving quality of life, gait speed, spatial cognition and executive function. Conclusion: The Tango dance intervention is a promising, non‐pharmaceutical intervention for African American women AD caregivers, for preservation of physiological, psychological and cognitive health.